Análisis de la educación financiera y su efecto en las finanzas personales de funcionarios del nivel ejecutivo de la Policía Metropolitana de Bogotá (2022)
Financial education allows the development of skills that affect a person's economic decision making; therefore, in their quality of life, hence the need for everyone to be knowledgeable about topics that achieve a successful management of financial resources, especially in adults, whose decisions can affect their well-being, that of their family and their environment. For the executive level officers of the Metropolitan Police of Bogota it is also important to have financial knowledge and skills, which makes it necessary to analyze their financial education, first making a general characterization, and then describing their financial habits, thus identifying the aspects to improve, aspects that resulted more at the moment of choosing financial products and in the control of expenses, than in the conceptualization itself, that is to say, in the application of their knowledge. The above implies that it is an analysis of a specific situation, making the research to be classified as qualitative, developed in three phases: observation, application and analysis and interpretation of the results. Within the research process, taking advantage of the benefits of information technologies, use is made of databases for the consultation of the theoretical framework, as well as for the application of the instruments, taking the results to the Power Bi tool for their respective analysis.